A wavelet approach in high performance visualization of digital mammograms using distributed parallel computation / Prof. Dr. Arsmah Ibrahim ... [et al.] - Ibrahim, Arsmah; Alias, Norma; Othman, Khairil Iskandar; Jayes, Mohd Idris; Salikin, Md Saion; Sulaiman, Hanifah (Research Management Institute (RMI), 2012)
Beowulf is a machine dedicated to parallel computing that gives better price/performance ratio as it is built from off the shelf components and runs mainly free software. One can build a Beowulf system using standard Linux distribution without any additional software (Sterling et al., 1999). Norma et.al (2003, 2005) from the Mathematics Department in UTM successfully set a Linuxbased Beowulf cluster called NORMA for high performance computation with 38 CPUs. Hanifah (2007) successfully set up a Linux-based Beowulf cluster called ARS with 8 CPUs in the Mathematics Department of UiTM which is ready to do high performance computations. These clusters can be used for intermediate and large scale mathematical problems that are inefficient or ineffective for single processor computers to compute. Both clusters can be used for writing parallel programs using MPI allowing multiple programs be run simultaneously to generate output from different simulation runs.